Determinants of Tax Planning: Theoretical Analysis - Matusevičienė, Lina; Rudžionienė, Kristina (Buhalterinės apskaitos teorija ir praktika, 2021)
Annotation. Tax planning is a topic of interest for taxpayers, practitioners, public authorities and academics. Analyzing scientific literature on tax planning shows that some authors are looking at the tax planning process, while others are looking at the factors that determine tax planning. Although there are a number of scientific literature analysing these factors, it is noted that there is a need to systematize this literature. The purpose of the article is to identify the determinants of tax planning activities in companies and households. Methods used in the article: systematic analysis of scientific literature, systematization of information, comparison, generalization. After analyzing the scientific literature, authors provide a concept of tax planning and selected determinants that encourage and inhibit the involvement of both types of taxpayers in tax planning activities. After a theoretical analysis, it was found that corporate tax planning is influenced by the company’s profitability, profit begor taxes, internationalisation, the scale of foreign operations, listing, capital receptivity and growth, development, size and leverage of the company, optimism of the company CEO, experience of his military service, lobbying, reputation and financial accounting issues. Household tax planning is influenced by taxpayers’ age, income, intra-household income inequality, experience, a compendium tax system, its complexity, fines, the likelihood ofecassionisation. Religiousity is a factor that hampers the involvement of both businesses and households in tax planning activities. Keywords: tax planning, determinants, tax avoidance, households, company. JEL Code: H26